Antioxidant and Hypoglycemic Activity of Sacha Inchi Meal Protein Hydrolysate - Tianyu Shu; Kai Wang; Xuewu Zhang (Applied Sciences, 2023)
Sacha inchi meal (SIM) is the residue from the processing of the oil crop sacha inchi. In the present study, biological enzymolysis was performed on SIM protein to obtain hydrolysates, and then the antioxidant and hypoglycemic activities were evaluated. The results showed that the scavenging rates of alkaline protease hydrolysate (SAl) and protamex hydrolysate (SPr) to ABTS free radicals were close to that of vitamin C at 5 mg/mL, amounting to 99.83 ± 0.33% and 100.00 ± 0.09%, respectively. The dipeptidyl peptidase (DPP-IV) inhibitory activities of SPr and SAl were also the highest, at the concentration of 2.5 mg/mL, their inhibition rates were 74.15 ± 0.68% and 56.38 ± 1.51%, respectively, with the IC50 values of 1.007 mg/mL and 2.130 mg/mL, respectively. Moreover, compared with the model group, all the hydrolysates increased the glucose consumption by 187.01–348.79% (at 800 μg/mL) in insulin-resistant HepG2 cells, which were better than positive drug Metformin. In conclusion, SIM protein hydrolysates have significant antioxidant and hypoglycemic activity in vitro; therefore, the hydrolysates could be used as for functional food and pharmaceutical development.